Triboelectrification Based on the Waste Waterproof Textiles for Multisource Energy Harvesting (Adv. Sustainable Syst. 5/2025) - Kushal Ruthvik Kaja; Sugato Hajra; Swati Panda; Mohamed Ahmed Belal; Phakkhananan Pakawanit; Naratip Vittayakorn; Chris Bowen; Hamideh Khanbareh; Hoe Joon Kim (Advanced Sustainable Systems, 2025)
Multisource Energy Harvesting In article number 2400678, Sugato Hajra, Hoe Joon Kim, and co-workers turn discarded waterproof textiles into innovative energy solutions. By creating triboelectric nanogenerators from waste, they harness wind, water, and motion to power sensor networks. This eco-friendly tech reduces waste and promotes sustainable energy in daily life.
Keywords: Green IT and Sustainability; Recycling and Waste Management Techniques; Electric Vehicles and Infrastructure